Macro-regional integration - new scales, spaces and governance for Europe? - Sielker, Franziska (My University, 2017)
Die Arbeit geht der Fragestellung nach, inwiefern das noch junge Kooperationsformat für Großräume in Europa zu neuen Ebenenbezügen (scales), neuen Raumbezügen (spaces) oder neuen Governanceformen führt. Im Jahr 2016 entstanden vier Makroregionen: die Ostseeregion, die Donauregion, die Adriatisch-Ionische Region und die Alpenregion. Die Kooperationen beziehen sich auf verschiedene Politikfelder wie zum Beispiel Transport, Umweltschutz oder Bildung. Angesiedelt zwischen der Ebene der EU und den Nationalstaaten bauen sie auf bestehenden Governancestrukturen auf. Es ist Ziel der Arbeit makroregionale Kooperationen zu charakterisieren und ihre Einflüsse auf europäische Integrationsprozesse, Raumpolitiken und politische Prozesse (policy styles) mit Hilfe von Fallbeispielen herauszuarbeiten. Konzeptionell wurden die durch makroregionale Strategien ausgelösten Entwicklungen unter den Gesichtspunkten von Europäischer Integration, Europäisierung, Territorialisierung/ Reterritorialisierung und scale/rescaling (Verschiebung von Maßstäben) in sechs Artikeln reflektiert. Die Arbeit kommt zu dem Ergebnis, dass makroregionale Governance vorrangig intergouvernemental organisiert ist. Eine formale Kompetenzverlagerung und damit Etablierung einer neuen makroregionale Ebene als neue "staatliche Ebene" findet nicht statt.

This dissertation seeks to better understand the implications of the development of macro-regional strategies for regions with common challenges for policy-making and European spatial governance. By 2016, four macro-regional strategies have been developed for the Baltic Sea, Danube, Adriatic-Ionian and Alpine regions raising expectations as to a new trend of macro-regional integration in Europe. The overall goal is to examine this new type of cooperation s characteristics, as well as the changes that transpire through these developments for integration dynamics, spatial governance and policy styles in European territorial cooperation. In a series of six articles, the thesis analyses the macro-regional dynamics through four conceptual lenses, two rooted in human geography (scale/rescaling and territoriality/reterritorialisation) and two rooted in political science (European integration and Europeanisation). The thesis answers, first, the question to what extent macro-regions indicate processes of Europeanisation of policies and rescaling. Second, the thesis questions macro-regional characteristics and their governance, and to what extent they create territorial meaning. Third, the thesis questions which forms of European integration and governance are displayed by macro-regions and how EU integration changes with the development of macro-regions. Empirically, the research approaches the investigation through the analysis of the Danube, Alpine and North Sea case studies. The dissertation examines the strategy for the Danube Region in-depth and exemplary traces the processes of activities in the Priority Area responsible for waterway infrastructure in the course of the FAIRway project development. Following the analysis, macro-regions are to be viewed as predominantly intergouvernmentally organised with selective supranational features. The thesis identifies macro-regions as soft spaces, leading to new soft borders, which, however, do not develop towards an own institutionalised statehood scale with formal territorial mandates.
Keywords: Raumordnung; Raumentwicklung; Raumwissenschaft; Regionalpolitik; Großraum; Planungsraum; Kooperation; Kohäsion; Makroregion; Raumentwicklungskonzept; Regional Governance; Grenzüberschreitende Raumordnung; Grenzüberschreitende Zusammenarbeit